A filter-less robust controller for damping SSCI oscillations in wind power plants - Nia, Hamed Khalili; Salehi, Farshid; Sahni, Mandhir; Karnik, Neeraj; Yin, Haiping (2017 IEEE Power & Energy Society General Meeting, 2017)
SSCI oscillations in wind power plants connected to series compensated networks has been the subject of significant research over the last decade. A major portion of this research has focused on methodologies to adequately characterize the SSCI issue and mitigate the same predominantly via turbine level controller augmentation solutions. In this paper, a filter-less robust damping controller named Power System Sub-synchronous Oscillation Damper (PSSOD) is proposed for mitigating SSCI concerns for wind power plants. An active filter-less controller design that presents low impedance in the entire sub-synchronous frequency range and high impedance at the nominal 60Hz frequency is presented. Frequency scan and time domain based simulations have been used across a wide range of operating conditions to underline the robustness and effectiveness of the PSSOD in terms of SSCI mitigation.